2021
DOI: 10.12982/cmujns.2021.035
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Nutritional Properties of Nixtamalized Quality Protein Maize Flour and its Potential as Substitute in Philippine Salt Bread

Abstract: Nixtamalization is an ancient method of processing corn that is said to enhance the nutritional value of maize by improving protein quality, increasing calcium and niacin bioavailability, and reducing phytic acid levels, thus increasing iron digestibility and biovailability. The main objective of this study was to determine the effect of different nixtamalization processes on the physicochemical and nutritional properties of quality protein maize (QPM) flour and evaluate its potential and acceptability as a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The results indicated by Farinde (2019) depicted that nixtamalisation improved niacin, lysine and available lysine in the treated QPM flour. A significant decline in the antinutrients, crude fat, nitrogen‐free extract and insoluble fibre contents of QPM flour was observed in nixtamalised samples (Sunico et al ., 2021). Studies conducted by Guria (2006) indicated that the in vitro protein digestibility of the QPM flour was found quite higher than normal maize.…”
Section: Macronutrient Profile Of Quality Protein Maizementioning
confidence: 99%
“…The results indicated by Farinde (2019) depicted that nixtamalisation improved niacin, lysine and available lysine in the treated QPM flour. A significant decline in the antinutrients, crude fat, nitrogen‐free extract and insoluble fibre contents of QPM flour was observed in nixtamalised samples (Sunico et al ., 2021). Studies conducted by Guria (2006) indicated that the in vitro protein digestibility of the QPM flour was found quite higher than normal maize.…”
Section: Macronutrient Profile Of Quality Protein Maizementioning
confidence: 99%
“…Moreover, IPB Var 6 flour has been used in combination with other starchy foods like rice, wheat flour, and sweet potato to produce more nutritious food products (Hernandez et al, 2022;Juanico & Hurtada, 2019;Maloles & Hurtada, 2018;Nguyen-Orca et al, 2014;Sunico et al, 2021;Tabuac et al, 2019).…”
Section: Novelty Impact Statementmentioning
confidence: 99%
“…IPB Var 6 contains 66.2% more lysine than regular local white corn and has significant amounts of minerals and phytochemicals such as iron (3.72 mg/100 g), zinc (2.37 mg/ 100 g), potassium (228 mg/100 g), calcium (72.16 mg/100 g), magnesium (137 mg/100 g), total phenolics (4.18 g GAE/100 g), total flavonoids (5.29 mg CE/100 g), and total carotenoids (0.73 mg/100 g) (Purificacion et al, 2018). Moreover, IPB Var 6 flour has been used in combination with other starchy foods like rice, wheat flour, and sweet potato to produce more nutritious food products (Hernandez et al, 2022; Juanico & Hurtada, 2019; Maloles & Hurtada, 2018; Nguyen‐Orca et al, 2014; Sunico et al, 2021; Tabuac et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process involves cooking corn in an oversaturated alkaline solution, typically, calcium hydroxide solution, for 30–40 min followed by steeping for 8–16 h. The cooked corn kernels, called nixtamal, are rinsed to remove excess lime and ground ( Serna-Saldivar and Rooney, 2015 ; Niu and Hou, 2020 ). This technique dissolves the hemicellulose, alters its rheological properties, promotes protein bonding, reduces antinutrients and aflatoxins to enhance the dietary value of cereals ( Schaarschmidt and Fauhl-Hassek, 2019 ; Cabrera-Ramírez et al, 2020 ; Kamau et al, 2020 ; Luzardo-Ocampo et al, 2020 ; Sunico et al, 2021 ). The nixtamalization method has also been investigated as a technology for increasing the number of phenolic chemicals in food ( Salazar-López et al, 2018 ).…”
Section: Innovative Processing Technologies To Increase the Phenolic Compounds In Cereal Branmentioning
confidence: 99%